RELATIONSHIP OF SPIRITUAL-WELLBEING WITH ANXIETY AND DEPRESSION IN PATIENTS WITH CARDIAC HEART DISEASE - Aan Nuraeni; Ristina Mirwanti; Anastasia Anna (Belitung Nursing Journal, 2018)
Background: Anxiety and depression are problems faced by patients with chronic diseases such as patients with Coronary Heart Disease (CHD). Both of these can also worsen the condition of CHD patients, thus needs to be prevented and handled. It is stated that spirituality can enhance constructive coping skills in patients with chronic diseases. But how it relates to anxiety and depression in patients with CHD in Indonesia is still unknown. Objective: The study purpose was to identify the relationship of spiritual wellbeing with the incidence of anxiety and depression in CHD patients. Methods: The research used descriptive correlative quantitative with cross sectional approach. The instruments used to measure the variables were Zung Self-rating Anxiety Scale, Beck Depression Inventory II, and Spirituality Index of Well-Being scale. Data were taken on 100 respondents within three months in outpatient cardiac unit with the consecutive sampling technique and analyzed by Spearman correlation test. Results: The mean of anxiety, depression, and spiritual well-being respectively were 47.66, 43, and 60. Based on Spearman test, spiritual wellbeing was correlated with anxiety significantly p= 0.000(r=-0.371) and so was depression p= 0.000 (r=-0.571). Conclusions: There was a significant relationship between spiritual well-being with anxiety and depression with negative correlation direction. The higher the spiritual well-being, the lower the level of anxiety and depression will be. Thus, nurses need to strengthen the spiritual aspects of CHD patients to prevent psychosocial problems.